A Gold Needle Tip Array Ultrafast Electron Source with High Beam Quality - Brückner, Leon; Nauk, Constantin; Dienstbier, Philip; Gerner, Constanze; Löhrl, Bastian; Paschen, Timo; Hommelhoff, Peter (2024 37th International Vacuum Nanoelectronics Conference (IVNC), 2024)
Nanometer-sharp needle tips are the electron sources with the highest beam quality. However, for a single needle tip, the total emission current is limited. Combining multiple needles into an array of tips should allow for higher currents while preserving the properties of the individual emitters. Previous studies on tip arrays have shown impressive emission character-istics, but could not demonstrate favourable transversal beam properties such as a well-behaved spot shape or low emittance. Here, we introduce an ultrafast electron source composed of a lithographically fabricated array of nanometer-sharp gold tips illuminated by 25 fs laser pulses. By harnessing the emission of multiple needles, we achieve a high-current electron beam while preserving individual emitter properties. Our source delivers up to 2000 electrons per pulse at moderate laser peak intensities of 10 11 w /cm 2 , with a narrow energy width of 0.5 ± 0.05 eV and a well-behaved Gaussian profile. The resulting electron beam exhibits high collimation and a small normalized emittance on the order of nm.rad, making it ideal for applications requiring both high current and spatial resolution, such as free-electron light sources and chip-based particle accelerator

A Gold Needle Tip Array Ultrafast Electron Source with High Beam Quality - Brückner, Leon; Nauk, Constantin; Dienstbier, Philip; Gerner, Constanze; Löhrl, Bastian; Paschen, Timo; Hommelhoff, Peter (Nano Letters, 2024)
Electron sources are crucial elements in diverse applications such as electron microscopes, synchrotrons, and free-electron lasers. Nanometer-sharp needle tips are electron emitters with the highest beam quality, yet for a single needle the current is limited. Combining the emission of multiple needles promises large current yields while preserving the individual emitters’ favorable properties. We present an ultrafast electron source consisting of a lithographically fabricated array of sharp gold tips illuminated with 25 fs laser pulses. The source provides up to 2000 electrons per pulse for moderate laser peak intensities of 1011 W/cm2 and a narrow energy width of 0.5 ± 0.05 eV at low current. The electron beam has a well-behaved Gaussian profile and is highly collimated, yielding a small normalized emittance on the order of nm·rad. These properties are well suited for applications requiring both high current and spatial resolution, such as free-electron light sources and chip-based particle accelerators.<br
Keywords: nano-optics; ultrafast electron emission; field enhancement; lasers; electron sources

Electronic Coherence and Coherent Dephasing in the Optical Control of Electrons in Graphene - Heide, Christian; Eckstein, Timo; Boolakee, Tobias; Gerner, Constanze; Weber, Heiko B.; Franco, Ignacio; Hommelhoff, Peter (Nano Letters, 2021)
Electronic coherence is of utmost importance for the access and control of quantum-mechanical solid-state properties. Using a purely electronic observable, the photocurrent, we measure a lower bound of the electronic coherence time of 22 ± 4 fs in graphene. The photocurrent is ideally suited to measure electronic coherence, as it is a direct result of coherent quantum-path interference, controlled by the delay between two ultrashort two-color laser pulses. The maximum delay for which interference between the population amplitude injected by the first pulse interferes with that generated by the second pulse determines the electronic coherence time. In particular, numerical simulations reveal that the experimental data yields a lower bound on the electronic coherence time, masked by coherent dephasing due to the broadband absorption in graphene. We expect that our results will significantly advance the understanding of coherent quantum control in solid-state systems ranging from excitation with weak fields to strongly driven system
Keywords: graphene; quantum-path interference; electronic coherence time; quantum control

From strong-field physics in and at nanoscale matter to photonics-based laser accelerators - Kozak, Martin; Higuchi, Takuya; McNeur, Joshua; Shiloh, Roy; Heide, Christian; Paschen, Timo; Yousefi, Peyman; Sturm, Constanze; Li, Ang; Illmer, Johannes; Meier, Stefan; Schönenberger, Norbert; et al. (205, 2019)
New ways of controlling quasi-free and free electrons by means of phase-controlled ultrashort laser pulses are demonstrated: from strong-field physics in the conducting 2-d material graphene and at the surface of nanostructures, to laser acceleration of free electrons with a nanophotonic structure, and the demonstration of the longitudinal Kapitza-Dirac effec